Analogy and Exemplary Reasoning in Legal Discourse - Kaptein, Hendrik; Velden, van der, Bastiaan (Amsterdam University Press, 2018)
This book brings together contributions from leading figures in legal studies on analogy and related forms of reasoning in the law. Analogical reasoning-which relies on the concept of two different things being in some way like each other-is hugely important not just in the practice of law, but it is nonetheless strongly contested.